Growth factor release and enhanced encapsulated periodontal stem cells viability by freeze-dried platelet concentrate loaded thermo-sensitive hydrogel for periodontal regeneration - Mohamed M. Ammar; Gihan H. Waly; Sayed H. Saniour; Taheya A. Moussa (Elsevier, 2018)
Periodontium regeneration is a highly challenging process as it requires the regeneration of three different tissues simultaneously. The aim of this study was to develop a composite material that can be easily applied and can sufficiently deliver essential growth factors and progenitor cells for periodontal tissue regeneration.Freeze-dried platelet concentrate (FDPC) was prepared and incorporated in a thermo-sensitive chitosan/β-glycerol phosphate (β-GP) hydrogel at concentrations of 5, 10, or 15 mg/ml. The viscosity of the hydrogels was investigated as the temperature rises from 25 °C to 37 °C and the release kinetics of transforming growth factor (TGF-β1), platelet-derived growth factor (PDGF-BB) and insulin-like growth factor (IGF-1) were investigated at four time points (1 h, 1 day, 1 week, 2 weeks). Periodontal ligament stem cells (PDLSCs) were isolated from human third molars and encapsulated in the different hydrogel groups. Their viability was investigated after 7 days in culture in comparison to standard culture conditions and non FDPC-loaded hydrogel.Results showed that loading FDPC in the hydrogel lowered the initial viscosity in comparison to the unloaded control group and did not affect the sol-gel transition in any group. All FDPC-loaded hydrogel groups exhibited sustained release of TGF-β1 and PDGF-BB for two weeks with significant difference between the different concentrations. The loading of 10 and 15 mg/ml of FDPC in the hydrogel increased the PDLSCs viability significantly compared to the unloaded hydrogel and was comparable to the standard culture conditions.Accordingly, it may be concluded that loading FDPC in a chitosan/β-GP hydrogel can offer enhanced injectability, a sustained release of growth factors and increased viability of encapsulated stem cells which can be beneficial in periodontium tissue regeneration. Keywords: Periodontal regeneration, Thermo-sensitive hydrogel, Chitosan, Platelet concentrate, Growth factors